Authorities who care: The Lutheran Doctrine of the Three Estates in Danish Legal Development from the Reformation to Absolutism. Issue 4 (8th August 2019) - Koefoed, Nina Javette
Abstract : This article argues that Luther's doctrine of the three estates gradually came to structure Danish legislation following the Reformation and through this the way in which society and social order were imagined. An essential element of the doctrine of the three estates was its understanding of authority, drawing on Luther's explanation of the fourth commandment as consisting of mutual obligations. Parallel with the integration of the three estates doctrine as structuring legislation, it was integrated in childhood teaching and taught ordinary people through the Catechism and the Table of Duties. A connected development was a shift in focus from the sixth to the fourth commandment as the basis for protecting marriage and the household through legislation. This change, the article argues, reflected the same understanding of authority and its obligation as the doctrine of the three estates.